(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1993)
Twelve species of Permian and Triassic Spiriferida and Athyridida from various localities and formations have been analysed in order to provide new data on the uhrastructure of these brachiopods. Ultrastructural analysis of the genus Tetractinella has provided new elements (e.g. the thickness of the secondary layer, the transverse profile of the secondary layer fibres and their thickness) that enable distinction between the species T. trigonella and T. hexagonalis. Ultrastructural features, such as the shape and the dimensions of the secondary layer fibres, have also led to the ultrastructural differentiation of three species of the genus Trigonotreta (Trigonotreta sp., T. stokesi and T. lyonsensis). Furthermore the ultrastructure of Clavigera bisulcata, Elivina tibetana, Spiriferella rajah, Spirelytha petaliformis, Martinia tschernyschewi and Mentzelia mentzeli has been investigated for the first time and new dtta on "Retzia" beneckei are provided.